Vitamin bio-fortification of cereals for food security - Naqvi S.; Gómez-Galera S.; Capell T.; Stoger E.; Christou P.; Zhu C. (Cereal science and technology for feeding ten billion people: genomics era and beyond, 2008)
The objective of the project is to engineer cereal plants with appropriate genes to obtain grains with an enhanced nutritional profile for vitamins for food security targeting specifically developing countries. Our focus is vitamins A, C, E and folate. Target species are rice and maize. The genetic constructs will be co-transformed simultaneously into appropriate target tissue by particle bombardment. We will generate a combinatorial population of plants that express different permutations and numbers of the input transgenes. Past experience indicates that if we generate ca. 100 independent transgenic plants there is a high probability of recovering a number of independent transformants expressing the full complement of transgenes. Transgenic plants will be screened for gene expression at the mRNA, protein and metabolite levels. We will present an update of our work and in the process we will paint a comprehensive picture of the molecular and genetic makeup of this population. This will be invaluable for food security applications and also for developing a better understanding of the mechanisms and factors that influence multiple transgene integration and expression in important cereal crops.
Meeting of the Eucarpia Cereal Section, 2006/11/13-17, Lleida (Spain)